Evaluation of Thermodynamic and Optical Properties of Sixteen Ionic Liquids at Different Temperatures - Ramakant; Shrivastava, Subhash C.; Srivastava, Shekhar; Pandey, Jata Dhari (Current Physical Chemistry, 2021)
Introduction: Based on the dimensional analysis, ρ -u- thermodynamic and ρ -uoptical properties correlations have been applied to sixteen ionic liquids at different temperatures. The objective of the present work is to employ these relations to ionic liquids. The experimental values of ρ and u have been reported in the literature at different temperatures. We have computed thermal expansivity (α), isothermal compressibility (βT), heat capacities ratio (γ), internal pressure (Pint), pseudo-Grüneisen parameter (), the energy of vaporization (ΔEV), enthalpy of vaporization (ΔHV), cohesive energy density (ced), solubility parameter (δ), refractive index (n), molar refraction (RM) and polarisability (αp) for these liquids. Methods: Correlations between density-sound velocity and several thermodynamic properties have been derived on the basis of dimensional analysis On the basis of dimensional analysis, a number of useful and important thermodynamic relations were deduced in terms of density (ρ) and speed of sound (u). Results: Results were found to be quite satisfactory. Keeping in view = uncertainty in the experimental values of ρ and u, as well as some approximations used, the agreement between experimental and theoretical values was found to be quite satisfactory. Discussion: Density (ρ) and ultrasonic speed (u) data of sixteen RTILs at different temperatures have been taken from the literature. Calculated values of α, βT, Pint, γ, CP-CV, and, were obtained from empirical relations. The experimental values of α were given for making a comparison. Conclusion: Based on the dimensional analysis, our recently developed correlations between ρ-u- thermodynamic and ρ-u- optical properties have been found to be quite successful when applied to sixteen ionic liquids for the first time. α, βT, γ, Pint, ΔEVap, ΔHVap, ced, δ as well as RM and αp were calculated at various temperatures.
Keywords: internal pressure (Pint)